Characteristics of agricultural entrepreneurs and their Agribusinesses in Sub-saharan africa: evidence from Benin - Kpenavoun Chogou, Sylvain; THOTO, Fréjus; honfoga b, Barthelemy G.; Houessou, Donald (My University, 2021)
Entrepreneurship in the sub-Saharan African agricultural sector has been growing in recent years because of increasing unemployment and underemployment. In Benin, policies and programs are encouraging individuals to start their own agribusinesses. To further sharpen these policies and programs to improve agricultural entrepreneurship's contribution to the economy, it is essential to avail information on the entrepreneurs, their businesses, and the typologies of agribusinesses. Such information is limited, which reduces the ability to develop evidence-informed policies and programs. This research aims to fill the gaps by describing the features of agricultural entrepreneurs in Benin. A random sample of 819 agricultural entrepreneurs was used, and data were collected on entrepreneurs and their businesses. Descriptive analysis and hierarchical clustering of principal components were performed. The study found that women’s participation in agricultural entrepreneurship in terms of new business formation is still low. Also, the agricultural entrepreneurs are more driven by necessity than opportunity, although they have a highly positive personality, mainly in terms of optimism and risk. At the enterprise level, most agribusinesses have been in operation for more than three years, but only one out of ten entrepreneurs felt that their business was at a mature phase. The research also evidenced that informality in the agribusiness sector is high because almost half of the agribusinesses were not registered with any formal governmental entity, and only three out of ten complied with tax regulations. Agricultural entrepreneurs were active in knowledge networks to expand their activities and improve their performance. Three categories of agribusiness were defined with the cluster analysis: ‘informal agribusinesses’ essentially built for profit, not registered, and owned by not highly educated adult entrepreneurs; ‘professional new agribusinesses’ were mainly operated by young entrepreneurs with a university education and agricultural professional training; and ‘mature agribusinesses’ were mostly formally registered and owned by highly educated entrepreneurs. This research will be instrumental for policymakers and practitioners to better understand agricultural entrepreneurship and improve its economic outcomes. It provides a strong evidence base to support the ongoing motivation of policymakers to provide solutions to unemployment and underemployment through agricultural entrepreneurship.
Keywords: agriculture; entrepreneurship; agribusiness; typology; cluster analysis; formalization; knowledge networks; Benin